1983
DOI: 10.1037/0022-0167.30.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Nonassertiveness of Asian Americans: An inaccurate assumption?

Abstract: Tested the view that Asian Americans are nonassertive and the possibility that they display differential assertiveness depending on situational variables. To determine if race of the individual with whom they are interacting is an influencing variable on assertion in Asian Americans, 51 Chinese-American and 25 Caucasian undergraduate males were randomly assigned to 1 of 2 conditions: role playing a series of 13 situations requiring assertion with an Asian experimenter or role playing the same situations with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 29 publications
9
52
0
Order By: Relevance
“…They found that Asian Americans had significantly lower assertion scores for five of the 10 scales: Making Difficult Requests, Making Requests in Public, Expressing Compliments, Disagreement with Parents, and Expressing Annoyance to the Opposite Sex. Unlike Fukuyama and Greenfield, who made a generalized statement about Asian American nonassertiveness, Sue et al (1983) pointed out that their Asian American sample displayed "situational nonassertiveness." For example, their Asian American subjects were found to be assertive in some situations such as in informal settings or when with members of their own ethnicity.…”
Section: Literature Reviewmentioning
confidence: 88%
See 2 more Smart Citations
“…They found that Asian Americans had significantly lower assertion scores for five of the 10 scales: Making Difficult Requests, Making Requests in Public, Expressing Compliments, Disagreement with Parents, and Expressing Annoyance to the Opposite Sex. Unlike Fukuyama and Greenfield, who made a generalized statement about Asian American nonassertiveness, Sue et al (1983) pointed out that their Asian American sample displayed "situational nonassertiveness." For example, their Asian American subjects were found to be assertive in some situations such as in informal settings or when with members of their own ethnicity.…”
Section: Literature Reviewmentioning
confidence: 88%
“…In the present study, other non-Asian Americans besides Caucasians-such as African Americans-were included in the comparison group. Further, the existing empirical studies on this topic tended to compare Asian American students with non-Asian American students (Fukuyama & Grenfield, 1983;Sue, Ino, & Sue, 1983). Although these studies imply that the cultural characteristics found in the Asian American students may be manifested in other subgroups of Asian Americans, no empirical work has directly addressed these issues in first generation Asian American parents of children with DD.…”
Section: Journal Of Ethnic and Cultural Diversity In Social Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the GLOBE research study, China had a low societal practice score on assertiveness (Den Hartog, 2004). Also, Sue, Ino, and Sue (1983) found that the self-reported assertive behaviour of Chinese Americans was less than that of European Americans.…”
Section: Chinese and Us Cultural Differencesmentioning
confidence: 96%
“…Indeed, in the GLOBE research study, China had a low societal practice score on assertiveness (Den Hartog, ). Also, Sue, Ino, and Sue () found that the self‐reported assertive behaviour of Chinese Americans was less than that of European Americans.
Hypothesis 2: Chinese students (as opposed to US Caucasian students) will be less likely to choose communication options that are assertive or confrontational.
…”
Section: Introductionmentioning
confidence: 99%